Management Of English Learning To Improve Digital-Based Language Literacy Skills - Astirini Swarastuti; Budiyanto, Budiyanto; M Bambang Purwanto (International Journal of Education, Vocational and Social Science, 2024)
English learning management is an important thing to pay attention to because it is an important part of the English learning process. The purpose of this study is to obtain information and analyze about planning, organizing, implementing, evaluating, constraints and solutions in learning English students at Madrasah Aliyah Negeri (MAN) 1 Palangkaraya, Central Borneo. In this study, qualitative descriptive research was used which was intended to obtain information about English Learning Management to Improve Language Literacy of MAN Students. The results of this study researchers concluded that the management of English language learning to improve the language literacy of Madrasah Aliyah Negeri (MAN) 1 Palangkaraya students has been running in accordance with the applicable rules covering extracurricular aspects containing learning planning, organizing, implementing and evaluating learning.